Characterization of Accessions and Identification of Potential Markers for Yield in Cotton - RA MEENA; D MONGA; PUNIT MOHAN; K RATHINAVEL (Seed Research, 2026)
The present study was carried out to characterize 5882 accession of Gossypium hirsutum and 650 of G. arboreum under different evaluation programme on the basis of thirty three morphological characters and the accession for marker trait of the interest were screened. Ninety one accession of G. hirsutum with various marker characters such as red leaves, okra leave, red petal, spotted petal, cluster boll bearing habits, elliptic bolls, dwarf and compact height, khaki cotton, naked seed and fourteen accession of G. arboreum with character of spotted petal were identified. The superior accessions for yield among each group were also identified for utilization in cotton improvement programme.